Low leakage current of CdSe quantum dots/Si composite structure and its performance for photodiode and solar cell - Soylu, M.; Al-Ghamdi, Ahmed A.; El-Tantawy, E.; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Elsevier Sci Ltd, 2016)
The CdSe quantum dots were deposited on p type Si(100) substrate by spin coating process. CdSe quantum dots were selected as the interlayer to reduce the reverse-bias leakage current of heterojunction. Various junction parameters were determined from the current-voltage (I-V) and capacitance voltage (C-V) characteristics. Au/CdSe quantum dots/p-Si structure exhibits a fairly low leakage current density of 4.54 x 10(-9) A/cm(2) and a high rectification ratio of 3.1 x 10(6) at applied electric field of +/- 4V. Furthermore, I-V characteristics under illumination show strong photovoltaic (PV) behavior. These results are attributed to the low interfacial state density and defect density due to CdSe quantum dots at the interface. It is also evaluated that the Au/CdSe quantum dots/p-Si structure can be a potential candidate for photodiode and solar cell applications. (C) 2016 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: CdSe; Leakage current density, Illumination; Electrical properties